Surgical Management of Depressed skull Fracture - Ali, Mumtaz; Ali, Liaqat; Roghani, Inayat Shah (Journal of Postgraduate Medical Institute, 2011)
to study the outcome of surgical management of depressed skull fracture. This study was conducted form April 1995 to March 2001, in department of Neurosurgery PGMI/LRH, Peshawar. A total of 98 patients with depressed skull fracture, treated surgically were included in the study. it included patients operated for cosmetic reasons of functional outcome. Patients treated conservatively, secondary to fire arm injury and penetrating objects were excluded from the study. Details regarding the causes, duration and clinical conditions were documented X-ray skull were done in all cases. CT scan was done in 78 cases. After surgery patients were followed up for 9 months. Clinical exmination of the wound for sepsis, CSF leak, check up X-rays / CT scan and neurological assessment of patients was done on every visit. Depressed skull fracture is a common neuro-traumatic disorder. The commonest causes in our society are: fall from height and rood traffice accident. in time surgical management gives excellent results and leads to minimize the sequel of this condition. Most of the causes can be prevented just by adopting preventive measures. The condition can be treated in periphery hospital as well, if trained personals are available.